Respuesta :
The inverse for this operation would be to find the equation for "x" since it's the equation for "y." Inverse means reverse in direction or position. To find the inverse of "y = -3/(x+4) , you would need to start by using the order of operations. Here's where you start:
y = -3/(x+4)
Next, you want to get the (x+4) to the other side. Since it's being divided, multiply this number on both sides.
y = -3/(x+4) ⇒ (x+4)y = -3
Now, you need to get y on the opposite side. Divide both sides by y.
(x+4)y = -3 ⇒y÷ (x+4)y = -3 ÷ y
The y's cancel on the left, so you would have the equation:
x+4 = -3/y
Now to get x by itself, subtract 4 from both sides.
x+4 = -3/y
-4 -4
⇒x = -3/y -4 is your final answer.
y = -3/(x+4)
Next, you want to get the (x+4) to the other side. Since it's being divided, multiply this number on both sides.
y = -3/(x+4) ⇒ (x+4)y = -3
Now, you need to get y on the opposite side. Divide both sides by y.
(x+4)y = -3 ⇒y÷ (x+4)y = -3 ÷ y
The y's cancel on the left, so you would have the equation:
x+4 = -3/y
Now to get x by itself, subtract 4 from both sides.
x+4 = -3/y
-4 -4
⇒x = -3/y -4 is your final answer.
To find inverse function, you swap the y and the x, then solve for y:
[tex]x= \frac{-3}{y+4} [/tex]
[tex]y+4= \frac{-3}{x} [/tex]
∴ [tex]y= \frac{-3}{x} -4[/tex]
[tex]x= \frac{-3}{y+4} [/tex]
[tex]y+4= \frac{-3}{x} [/tex]
∴ [tex]y= \frac{-3}{x} -4[/tex]